2007
DOI: 10.1117/12.720924
|View full text |Cite
|
Sign up to set email alerts
|

Combined 3-D auditory-visual cueing for a visual target acquisition task

Abstract: Previous studies have shown that helmet-mounted displays (HMDs) are advantageous in maintaining situation awareness and increasing the amount of time pilots spend looking off-boresight (Geiselman & Osgood, 1994;Geiselman & Osgood, 1995). However, space is also limited on a HMD and any symbology that is presented takes up valuable space and can occlude a pilot's vision. There has been much research in the area of visual cueing and visual search as they relate to seeking out visual targets in the sky. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous research has shown 3D audio to be beneficial for visual target acquisition, both as a stand-alone spatial cue 18 and when combined with other visual cues such as the target locator cues discussed above. 19,20 …”
Section: Targetingmentioning
confidence: 98%
“…Previous research has shown 3D audio to be beneficial for visual target acquisition, both as a stand-alone spatial cue 18 and when combined with other visual cues such as the target locator cues discussed above. 19,20 …”
Section: Targetingmentioning
confidence: 98%